Komposisi Musik Semarak Sipai Bersumber Dari Beruji Dol Dalam Upacara Tabot Di Kota Bengkulu - Sandy Purwanda; desmawardi desmawardi; Asep Saepul Haris (Institut Seni Indonesia Padangpanjang, 2024)
Music is a means of expressing the soul to communicate and interact between living creatures. Through music we can express various ideas with various colors of sound produced by any object that can accommodate the idea itself. Sounds and voices are arranged well so that a musical work is created as a harbor for ideas that are full of messages and meaning. This work begins with research on the Bruji Dol performance and from the results of the analysis, a conclusion is drawn to take one part, namely the song Girik